2018
DOI: 10.29312/remexca.v9i3.1214
|View full text |Cite
|
Sign up to set email alerts
|

Características y productividad de una planta MAC, Agave tequilana desarrollada con fertigación en Tamaulipas, México

Abstract: En el cultivo de Agave tequilana, los estudios se han restringido a una parte de su largo ciclo y a periodos cortos de tiempo, por tal razón, con el objetivo de evaluar las características agronómicas en planta y piña en un ciclo completo de la planta, se establecieron hijuelos provenientes de Jalisco en el sur de Tamaulipas en tres condiciones: a) en temporal y sin fertilizante (TA); b) fertigación, además de la precipitación, recibieron agua y nutrimentos (N, P, K, Ca, Mg, y micronutrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
1
8
0
4
Order By: Relevance
“…of nutrient solution, water only (Tables 7 and 8). These data coincide with those of ZÚÑIgA-ESTRADA et al (2018) carried in the cultivation of Agave tequilana Weber when applied different concentrations of nutrient solution. Results of the relative growth rates of the variables evaluated, had the same behavior, the values increased when the nutrient content applied by fertigation was higher, that is, plants that received fertigation at 100% nutrient concentration reached larger sizes compared to plants that were only irrigated with water (Table 7).…”
Section: Source Of Variation Dfsupporting
confidence: 87%
“…of nutrient solution, water only (Tables 7 and 8). These data coincide with those of ZÚÑIgA-ESTRADA et al (2018) carried in the cultivation of Agave tequilana Weber when applied different concentrations of nutrient solution. Results of the relative growth rates of the variables evaluated, had the same behavior, the values increased when the nutrient content applied by fertigation was higher, that is, plants that received fertigation at 100% nutrient concentration reached larger sizes compared to plants that were only irrigated with water (Table 7).…”
Section: Source Of Variation Dfsupporting
confidence: 87%
“…Nobel et al (1988) observed that fertilization with N, P, K, and B enhanced growth and nocturnal CO 2 uptake of A. lechuguilla. Similarly, irrigation, in combination with fertilization with N, P, and K, increased foliar leaf area, leaf number, and concentration of sugars, particularly fructose and glucose in A. tequilana and Agave potatorum Zúñiga-Estrada et al, 2018). Valenzuela and Gonzalez (1995) found that fertilization of A. lechuguilla and A. tequilana with P and N increased leaf area.…”
Section: Soil-based Nutrients Underneath Rock Pilesmentioning
confidence: 96%
“…Agave crops have annual biomass productivities (kg ha -1 yr -1 ) ranging from 4000 to 30,000 and may have even greater potential productivities, depending on the agronomic cultivation system [21,[60][61][62]. The estimated annual productivity of Agave for Tequila The cultivated area decreased to 124,708 ha in 2014, but in the same year the productive area increased to 29,145 ha [36].…”
Section: Productivity Of Agavementioning
confidence: 99%